Pluralisme Agama dalam Perspektif Al-Qur’an; Kajian Tafsir Tah?lîlî dan Maud?û’î - Abdul Basid (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2015)
Pluralism is a necessity, something that can not be avoided in almost all aspects of life, religion is also not spared. Al-Qur’an has given a view of the attitude and way of dealing with religious pluralism. Bismillâhirrahmânirrahîm requires us to apply tolerance. More broadly, the message can be interpreted in a manner inverted, that every Muslims to avoid violence. To study the interpretation Tahlilî and Maudu’i, religious pluralism is essentially personal nature, but humans are asked to select and establish the religion. Tolerance is born of an awareness of the importance of respect for others. But pluralism want to go beyond these achievements, such as an effort to understand the other through a constructive understanding. That is, because of the differences and diversity is the real thing, it’s necessary to have a good understanding and full of other things.